10 Years Citation Analysis Of Dentistry Theses And Selected Scholarly Papers At Kerman University Of Medical Sciences - Maryam Okhovati; Azam Bazrafshan; Malihe Sadat Bazrafshan; Reza Malekpour Afshar (Tehran University of Medical Sciences, 2014)
Background and Aim: Scientific journals are the most major tools in disseminating research findings. With the increasing number and price of scientific journals, libraries need to select journals. Citation analysis is a practical method in identifying the best titles to be subscribed. This study was to identify core journals in the field of dentistry using citation analysis. Materials and Methods: Two hundered and seventy six documents including dentistry theses (241 titles) and faculty papers (35 titles) indexed in Science Citation Index (SCIE) were selected and their references were extracted and evaluated using citation analysis methods. The distribution frequency of journals confirmed the Bradford's Law of Scattering representing core dentistry journals. Results: Eleven thousand twenty three references were totally extracted. Average reference per theses and papers was 39/25 and 44/74, respectively. English journals and books were the most frequent referred documents having 95% of total references approximately. The most updated references were in English dated during 2001-2005 and 2006-2010. Using the Bradford's Law, five journals were introduced as core dentistry journals. Conclusion: Selecting and subscribing core journals leads into cost-effectiveness in libraries and plays an important role in meeting user's needs. While having many challenges in accessing scientific resources, core journals selection and subscription is an intelligent action resulting in effective use of financial resources.